ASSESSMENT IN THE SYSTEM OF ACCOUNTING SUPPORT OF NON-FINANCIAL ASSETS BUDGET MANAGERS - LARIKOVA, Tatiana (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The object of the study is the features of evaluation and revaluation in the accounting support of non-financial assets of budget managers. The problematic issues of the process of revaluation of groups of non-financial assets - fixed assets are specified, the peculiarities of reflection in the accounting system of revaluation or depreciation of non-financial assets are determined. The economic meaning of fair value as an important component of cost accounting in the process of further recognition of non-financial assets is clarified.An analysis of regulatory and legal support for the revaluation of non-financial assets. The method of accounting for the results of the first and subsequent revaluation is specified, the features of accounting for revaluation and revaluation in accordance with the NS(C)BGS 121 "Fixed assets", namely: accounting for the first revaluation; accounting for revaluation of previously discounted items; accounting for the first markdown; accounting for the revaluation of previously revalued items. Examples of accounting transactions for accounting for the results of revaluation of non-financial assets - fixed assets, which justifies the need to open analytical accounts. The structure of analytical accounts to separate sub-accounts in the context of revaluation of fixed assets is developed. which will allow you to track the results of the next revaluation, subject to a revaluation of previously discounted items of property, plant and equipment and a revaluation of previously revalued items.Updated factors that may be the basis for increasing the useful life of non-financial assets of budget managers, namely: 1. The expected probability that the budget manager will receive economic benefits from its use in the future; 2. The use of assets is assessed based on its potential utility for society; 3. Improving the object of assets, which leads to increased moral and physical depreciation.The peculiarities of documentation are studied, based on the results of revaluation of non-financial assets - fixed assets, it is proposed to keep a register on the formation of lists of fixed assets to be revalued; the main points for the formation of the revaluation order are marked; the form of the statement for the account of service life of fixed assets is developed.
Keywords: valuation; accounting; revaluation; depreciation; non-financial assets; fixed assets; fair value; budget manager